Regulation of total LC3 levels by angiotensin II in vascular smooth muscle cells. Issue 5 (3rd February 2022) - Mondaca‐Ruff, David; Quiroga, Clara; Norambuena‐Soto, Ignacio; Riquelme, Jaime A.; San Martin, Alejandra; Bustamante, Mario; Lavandero, Sergio; Chiong, Mario
Abstract: Hypertension is associated with high circulating angiotensin II (Ang II). We have reported that autophagy regulates Ang II‐induced vascular smooth muscle cell (VSMC) hypertrophy, but the mechanism mediating this effect is still unknown. Therefore, we studied how Ang II regulates LC3 levels in VSMCs and whether Bag3, a co‐chaperone known to regulate LC3 total levels, may be involved in the effects elicited by Ang II. A7r5 cell line or rat aortic smooth muscle cell (RASMC) primary culture were stimulated with Ang II 100 nM for 24 h and LC3 I, LC3 II and Bag3 protein levels were determined by Western blot. MAP1LC3B mRNA levels were assessed by RT‐qPCR. Ang II increased MAP1LC3B mRNA levels and protein levels of LC3 I, LC3 II and total LC3 (LC3 I + LC3 II). Cycloheximide, but not actinomycin D, abolished LC3 II and total LC3 increase elicited by Ang II in RASMCs. In A7r5 cells, cycloheximide prevented the Ang II‐mediated increase of LC3 I and total LC3, but not LC3 II. Moreover, Ang II increased Bag3 levels, but this increase was not observed upon co‐administration with either losartan 1 μM (AT1R antagonist) or Y‐27632 10 μM (ROCK inhibitor). These results suggest that Ang II may regulate total LC3 content through transcriptional and translational mechanisms. Moreover, Bag3 is increased in response to Ang II by a AT1R/ROCK signalling pathway. These data provide preliminary evidence suggesting that Ang II may stimulate autophagy in VSMCs by increasing total LC3 content and LC3 processing.